Correlation between Husband's Support and Primipara's Willingness to Provide Exclusive Breastfeeding - endangstikes - (Universitas Nahdlatul Ulama Surabaya, 2023)
Exclusive breastfeeding is the right of children and mothers. Unfortunately, the realization is not easy, especially for primipara. Several factors greatly influence its success, including the husband's support. This study aims to determine the correlation between husbands' support and mothers' willingness to provide exclusive breastfeeding. This research is an analytic descriptive with a cross-sectional approach. The population of this study was breastfeeding mothers at Yuni Astuti's Independent Midwife Practice, located in Sewon, Bantul, Yogyakarta, primiparous mothers with babies aged 0-6 months. Data was collected using a questionnaire consisting of 21 questions. Respondents' answers are indicated by statements of agreement on four scales (strongly agree, agree, disagree, strongly disagree). Univariate data were analyzed using percentages, and bivariate data using the Chi-Square test.  The research results find that the husband's support is related to the mother's willingness to provide exclusive breastfeeding. Mothers willing to give exclusive breastfeeding receive good support from their husbands. Although her husband's support strongly influences a mother's willingness to provide exclusive breastfeeding, several other variables still need to be considered. It is suggested that future researchers conduct a detailed study of the success factors of exclusive breastfeeding so that the public can take the results as a recommendation for mothers to do the same.